Bioclimatic Condition Variability in the Central Region of Poland in the Period 2001–2024 - Katarzyna Rozbicka; Tomasz Rozbicki; Grzegorz Majewski (Atmosphere)
This study investigates the variations in the Universal Thermal Climate Index (UTCI) calculated based on meteorological data from six synoptic stations across the Central Region of Poland from 2001 to 2024, focusing on spatial and temporal trends in thermal stress. The average annual UTCI was found to be 7.7 °C, indicating “slight cold stress,” with regional differences. Higher values were recorded in the west and northwest compared to lower values in the southeast. Maximum UTCI values associated with “very strong heat stress” exceeded 40.0 °C, while minimum values denoting “extreme cold stress” occurred in eastern cities more often. A linear trend analysis revealed a general increase in UTCI values across all stations, varying from 0.6 °C to 1.8 °C per decade, and showed distinct positive trends for heat stress categories, particularly “strong heat stress.” In contrast, a decrease in “strong cold stress” was observed. Favorable bioclimatic conditions, defined as “comfort”, predominated during most months, especially from April to October, while extreme thermal conditions were infrequently recorded. This research shows significant changes in thermal comfort and stress patterns, highlighting regional disparities and the implications for public health and urban planning in response to evolving bioclimatic conditions.